1982
DOI: 10.1021/ja00388a104
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy for neonatal jaundice. Stereospecific and regioselective photoisomerization of bilirubin bound to human serum albumin and NMR characterization of intramolecularly cyclized photoproducts

Abstract: Anders als bei der Bindung von (Z,Z)‐ Bilirubin IXa an tierischen Serum‐Albumin (SA) weist die an menschliches SA gebundene Titelverbindung bei ihrer Photoisomerisierung nur eines der beiden möglichen Diastereomeren auf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(66 citation statements)
references
References 0 publications
1
65
0
Order By: Relevance
“…The second fastest photoehemical reaction of bilirubin is structural isomerization to lumirubin (6). During phototherapy the serum concentration of lumirubin is lower than the concentration of the configurational isomers: 2 to 6 versus 15 to 20% of the total serum bilirubin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second fastest photoehemical reaction of bilirubin is structural isomerization to lumirubin (6). During phototherapy the serum concentration of lumirubin is lower than the concentration of the configurational isomers: 2 to 6 versus 15 to 20% of the total serum bilirubin.…”
Section: Discussionmentioning
confidence: 99%
“…However, serial sampling at 15-20 min intervals for 180 min from 14 individual fetuses (91-139 days) showed that TSH was secreted in a markedly exaggerated pulsatile manner compared to that observed after birth. The mean amplitude of TSH pulses fell (p < 0.005) from 5.9 2 8.1 pU/ml in the fetuses to 2.1 + 1.1 pU/ml in five neonatal lambs (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) days) and to 1.5 f 0.4 pU/ml in three adult nonpregnant ewes. The mean pulse frequency for the 14 fetuses was 0.7 + 0.3 pulses/h and was reduced (p < 0.001) to 0.3 + 0.1 pulseslh in lambs and to 0.3 f 0.1 pulses/h in the ewes.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Photooxidation may also occur (5,6). Due to increased polarity, these isomers can be excreted in bile and urine, bypassing the need for conjugation.…”
mentioning
confidence: 99%
“…Other bilirubin isomers, including bilirubin-III α and bilirubin-XIII α, were eliminated because their 1 H NMR spectra are substantially different (McDonagh et al, 1982).…”
Section: Proposed Researchmentioning
confidence: 99%